Phenotypic Detection of Macrolide, Lincosamide and Streptogramin B Resistance Among Staphylococcus Aureus Clinical Isolates in A Northern Nigeria Tertiary Hospital - Yahaya, Hassan; Ahmad, Ahmad Saad; Aminu Ibrahim,; Sharif Alhassan Abdullahi , (AlQalam Journal of Medical and Applied Sciences, 2022)
Background and aims. Staphylococcus aureus (S. aureus) is a frequently isolated pathogen associated with community and hospital infections. The emergence of Methicillin-Resistant S. aureus (MRSA) and macrolide–lincosamide–streptogramin B (MLSB) resistant strains pose a severe challenge to antibiotic selection. The study aimed to determine phenotypic MLSB resistant strains from clinical samples. Methods. Two hundred clinical samples from the wound, ear swab, urine, blood and sputum were collected. The occurrence of constitutive (cMLSB) and inducible (iMLSB) clindamycin resistance was phenotypically determined. A 31 non-duplicate, confirmed S. aureus were isolated and used. Antimicrobial susceptibility testing (AST) of the isolates was tested using six antibiotics; cefoxitin (30 µg), erythromycin (15 µg), clindamycin (2 µg), ciprofloxacin (5 µg), chloramphenicol (30 µg) and cotrimoxazole (25 µg). The MLSB resistance phenotype of the isolates, erythromycin-resistant isolates were assessed by double-disk diffusion (D-test) for detection. Results. Of the 31 isolates, 21 (67.74%) were methicillin-susceptible Staphylococcus aureus (MSSA) and 10 (32.3%) were MRSA. Out of 21 MSSA strains, 5 were MLSB resistant phenotypes, of which 1 (4.8%) and 4 (19.0%) strains showed cMLSB and iMLSB resistance respectively. However, 6 out of 10 MRSA strains detected showed MLSB resistance. Both cMLSB and iMLSB resistance showed 3 (30%). The result showed that MRSA, cMLSB and iMLSB resistance occurs in clinical isolates of S. aureus from the study area. Conclusion. The use of a simple and cost-effective method (disk diffusion) for cefoxitin and the D-test for iMLSB organisms could easily identify resistant isolates. Antibiotic resistance profiles determination could optimize the therapy of multi-drug resistant strains.